E-SPORT SELULER SEBAGAI PILIHAN PROFESI MAHASISWA/I FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS UDAYANA - Ginting, Yose Afry Lucky; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
This research was conducted with the aim of knowing and analyzing the location of the factors that influence a person in determining the choice of a profession to be engaged in. Through the analysis presented, this study seeks to provide a sociological explanation of the existence of the mobile e-Sport trend as a person's consideration in determining his profession. The research data were obtained through field observations, documentation, and interviews with five students at the Faculty of Social and Political Sciences, Udayana University who are active as mobile online game players. The phenomenon of mobile online games among students has mushroomed when mobile e-Sport competitions are crowded in big cities such as Denpasar. The high intensity of cellular e-Sport competitions in Denpasar makes the opportunity for cellular e-Sport players to channel their abilities to be high. Added to this is the impression of a prestigious cellular e-Sport because of the rising prestige of e-Sport where the public's view of e-Sport, especially cellular, is changing. With this opportunity, many students are finally taking part-time activities as mobile e-sports players. Furthermore, students view and interpret mobile e-Sports also have many views. There are those who feel that being a mobile e-Sport player is a promising profession, so they are very focused on the mobile e-Sport field. There are also those who interpret that being a mobile e-Sport is a trend or fashion that is developing because of the pride and feeling of being cool as a mobile e-Sport player. And there are also those who feel that their status is elevated because of the mobile e-Sport itself because it is indirectly recognized by others.  Keyword: Student, Rational Choice, Mobile e-Sport, Profession.